Uji Efek Pelindung Hati Ekstrak Air Tanaman Kulit Lawang, Cinnamomum Cullilaban (Lauraceae), melalui Pemeriksaan MDA dan SOD Plasma Sel Darah Tikus - Soeksmanto, Arif (Jurnal Natur Indonesia, 2011)
Industrial growth, pollution, and the change of life style cause environmental degradation. This condition enhancesthe occurrence of degenerative diseases that more difficult to conquer than infective diseases. This promotes theuse of herbs in America up to 385% in period 1990-1997, wasting 4–12 billion dollar each year. World HealthOrganization (WHO) estimates approximately 4 billion or 80% of world citizens use herbs for their health care. Kulitlawang plants are medicinal plants grown endemically in Papua and Maluku regions. The existence of the plants inMaluku islands is considered as endangered species. Information on the plants in scientific publication is relativelylimited. meanwhile Cinnamomum sp. is known having high antioxidant compound. This research aimed to find outhepatoprotector effect of kulit lawang water extract through observation of MDA and SOD of venous blood of ratintoxicated with CCl4. Dosage used was based on result of effective dosage test which showed that water extractof kulit lawang plant of 20 mg/kg bw as highest dosage that did not harm animal health. Result of hepatoprotectoreffect test showed that MDA and SOD of control were 230.12 U/ml and 1243.00 ρmol/ml, whereas water extract ofkulit lawang was 414.45 U/ml and 793.00 ρ mol/ml, á-tocopherol 416.42 U/ml and 782.33 ρmol/ml, and curcumin426.07 U/ml and 734.00 ρmol/ml. This showed that water extract of kulit lawang plant has antioxidant propertiesand potential as hepatoprotector of oxidative damage.